Rare Case of Takayasu Arteritis with Simultaneous Stenosis and Dilatation with Infrarenal Aortic Aneurysm - Nagpal, Anoop; Debi, Uma; Singh, Lokesh; Sandhu, M S (Cardiology and Cardiovascular Medicine, 2021)
Takayasu arteritis is a granulomatous vasculities involving aorta and its branches, leading to stenosis, thrombosis or sometimes aneurysm formation. Our patient is a 36 year old female presented clinically with symptoms consistent with arteritis and on imaging, shows presence of concurrent stenosis and aneurysmal dilation of right sided subclavian artery with dilatation of brachiocephalic trunk and celiac artery. It also demonstrated Saccular aneurysm with ulcerative plaques arising from the infrarenal aorta.